Primary intraosseous Rosai–Dorfman disease: An analysis of clinicopathologic characteristics, molecular genetics, and prognostic features - Weng, Xin; Yang, Yajie; Zhang, Meng; Cai, Chang; Sun, Yanhua; Wu, Xikang; Zhang, Rongrong; Gui, Huihui; Li, Wei; Xu, Qizhong; Liu, Xia (Frontiers in Oncology, 2022)
Background: Rosai-Dorfman disease (RDD) is a rare histiocytic proliferative disorder of uncertain pathogenesis. Most patients present with proliferation in the lymph nodes manifesting as adenopathy; however, RDD may primarily arise in a variety of extranodal sites, including bone, which is a great challenge to diagnosis. The clinicopathological characteristics and prognostic features of primary intraosseous RDD have not been well characterized. Methods: We retrospectively analyzed the clinicopathologic and prognostic features of 4 cases of primary intraosseous RDD during the past 10 years in our hospital, with review of an additional 62 cases with complete follow-up data from the literature. Results: Primary intraosseous RDD was identified in 0.14% (4/2800) of total bone biopsies performed at our institution over the study period. According to our retrospective analysis, a total of 18 cases of primary lymph node, skin, or other non-osseous site-based RDD were diagnosed in our hospital. The ages of the 66 total patients ranged from 1.5 to 76 years, with a median age of 25 years. There were 31 male and 35 female patients, with a male-to-female ratio of 0.89:1. Primary intraosseous RDD occurred most often in the bones of the extremities (60.6%, 40/66), with the proximal tibia being the most common location. 39.4% (26/66) of cases arose in the axial skeleton, predominantly in the vertebra and craniofacial bones. Immunohistochemistry showed that large histiocytes from patients with RDD were positive for OCT2, in addition to S100 and CD68.The survival data showed that 22.7% (15/66) of patients experienced recurrences or developed RDD at distant sites during the follow-up period (median follow-up, 13 months; range, 1–106 months). The 5-year progression-free survival (PFS) of patients with primary intraosseous RDD was 57.5%. Conclusion: Primary intraosseous RDD is an extremely rare disease. Diagnosis of RDD may be quite challenging because of its nonspecific clinical presentation and imaging. Immunohistochemistry showed that large histiocytes were positive for OCT2 in addition to S100 and CD68, which may be helpful for differential diagnosis. Molecular detection showed that RDD may be related to the MAPK pathway, though these results are also ultimately not specific.